Nutrient uptake and recovery potentials of Ocimum basilicum and Corchorus olitorius in a polyculture aquaponic system - Junaid, Azeezat Adenike; Kamarudin, Mohd Salleh; Junaid, Quazim Olawale; Edaroyati, Wahab Puteri; Isyaka, Mohammed Sani; Dauda, Akeem Babatunde; Umar, Danladi Muhammed; Igoli, John Ogbaji; Mohd Nurul Amin, Sarker (Elsevier, 2023)
The nutrient recovery potentials of the plants Ocimum basilicum and Corchorus olitorius in a polyculture aquaponic system were evaluated. Two treatments of polyculture aquaponics (fish + crayfish + O. basilicum; and fish + crayfish + C. olitorius) and a conventional recirculating aquaculture system (RAS) as the control (fish + crayfish) were set up in triplicates, randomly. The fish and crayfish were stocked at 75 fish:50 crayfish per treatment while three seedlings of each plant were placed in each planting cup. There were five plant throughs with each having 14 planting holes, making a total of 70 planting holes per treatment. The water quality parameters, growth performance and nutrients uptake of the fish, crayfish and plants were determined after 14 weeks observation. The results showed that the dissolved oxygen, electrical conductivity, total dissolved solids and nitrates in the culture tanks of both plant treatments were significantly higher than recirculating aquaculture system treatment, especially from eight weeks and above. The fish and crayfish in the O. basilicum-polyculture aquaponic system had higher final weight gain, 53.6 g and 14.8 g respectively, while higher survival rate (97.33 ± 0.77 and 82.67 ± 2.9, respectively), and lower feed conversion ratio (2.46 ± 0.06 and 2.68 ± 0.04, respectively) were observed in the RAS treatment, although there were no significant differences (P > 0.05) across treatments. The yield of O. basilicum (274 g m−2) was significantly higher than C. olitorius (213 g m−2), while the N-uptake by O. basilicum (128.4 g culture unit−1) was significantly higher than C. olitorius (102.2 g culture unit−1). However, there were about 37–41 of N, 38–41 of P and 44–48 of K after harvest which is an indication that aquaponics polyculture system can either accommodate more plant troughs (increase plant densities) or more planting cycle of the herbs.